FORMS OF PUBLIC-PRIVATE PARTNERSHIP (PPP) AND THEIR APPLICATIONS IN NIGERIA - T. E., Oyigbo; Ugwu, Prof. O. O.; Nnadi, Dr. EOE (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
It has become imperative to study the features of the various models with a view to ensuring suitable application with increased application of Public-Private Partnership (PPP) as the panacea for infrastructure development and maintenance in most states of the country, The research employed review research design of which available journals, reports, textbooks, gazettes and newspapers sourced the information needed. Literature reveals the need for increased awareness of PPP, which is capital intensive with potency of complicated legal tussle, if not properly understood. The paper also analyzed the challenges militating against the implementation of PPP agreements in the country. It is thus, recommended that stakeholders in the areas of PPP should be adequately trained and enabling laws domesticated in each state of the federation in order to develop public infrastructure in the current reality